Biotechnology and bioinformatics : advances and applications for bioenergy, bioremediation, and biopharmaceutical research - Thangadurai, D editor; Sangeetha, Jeyabalan editor (Oakville, Ontario : Apple Academic Press, 2015)
Includes bibliographical references and index.